Fracture strength of teeth with coronal destruction after core build-up restoration with bulk fill materials - Oliveira, Carlos Rangel de Moura [UNESP]; Reis, Érica Gouveia Jorge [UNESP]; Tanomaru-Filho, Mário [UNESP]; Reis, José Maurício dos Santos Nunes [UNESP] (Wiley, 2022)
Objective: This study aimed to evaluate the fracture strength and failure modes of different core techniques in teeth with simulated coronal destruction. Materials and methods: Forty teeth were endodontically prepared and the specimens were divided into four experimental groups (n = 10) according to the core composition: Filtek One Bulk Fill-FOBF, Filtek Z350 XT-FZ350 (standard group), Filtek Bulk Fill Flow-FBFF, and LuxaCore Z-LCZ. CAD/CAM Monolithic zirconia crowns were obtained and cemented with RelyX U200. After storage in distilled water at 37°C for 48 h, the specimens were subjected to thermal cycling and to compressive strength mechanical tests. Statistical analyses (α = 0.05) were performed by non-parametric Kruskal–Wallis, Dunn post hoc, and Fisher's exact tests. Results: No significant differences (p > 0.05) were observed among FOBF, FZ350, and FBFF (mean ranks = 20.30, 12.20, and 23.20, respectively). LCZ (mean rank = 26.30) produced results similar to those of FOBF and FBFF (p > 0.05) and higher than those of FZ350 (p = 0.042). The most frequent type of failure was irreparable, regardless of the experimental condition. The lowest percentages of reparable fractures were produced by FOBF group (10%). Conclusions: The use of bulk fill materials, including the “core-and-post” LCZ dual-cure resin composite, did not impair the fracture strength of endodontically treated teeth with coronal destruction. Clinical significance: Resin composite bulk fill materials that can be used as a core-and-post cementation in an only stage are interesting, since they enable clinicians to work with one only material, and avoid several materials interfaces, technical sensitivity, and longer chair-time due to multistep procedures.
Keywords: CAD/CAM; ceramics; dental materials; endodontics; prosthodontics